2021
DOI: 10.1108/ejim-10-2020-0425
|View full text |Cite
|
Sign up to set email alerts
|

Green innovation: a multidomain systematic review

Abstract: PurposeThis paper examines the status and evolution of green innovation research from 1948 to 2018.Design/methodology/approachUsing a systematic review of 293 peer-reviewed scholarly articles, the authors classify journal outlets, publication trends, research methods (research type, approach, design), themes/topics focus, country and regional distribution and theoretical perspectives, identifying main trends. They apply mixed methodologies, integrating both content and descriptive analyses.FindingsResults reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 109 publications
0
53
0
Order By: Relevance
“…On the new theory of consumer behavior [36] Consumer green preferences improve green innovation [37,38] Consumer environmental awareness and coordination in the closed-loop supply chain [39] Dual-channel green supply chain pricing policy considering consumers' green preferences [40] Table 1. Cont.…”
Section: Consumer Behavior Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…On the new theory of consumer behavior [36] Consumer green preferences improve green innovation [37,38] Consumer environmental awareness and coordination in the closed-loop supply chain [39] Dual-channel green supply chain pricing policy considering consumers' green preferences [40] Table 1. Cont.…”
Section: Consumer Behavior Theorymentioning
confidence: 99%
“…Studies have found that, as a result of the increasingly serious problem of environmental pollution, consumers are more willing to buy low-carbon, energy-saving, and environmentally friendly products. This behavior will change the product attributes of producers, prompt manufacturers to enhance their green innovation capabilities to produce green products, and promote the development of green industries [37,38]. Therefore, the green preferences of consumers have attracted great attention from the government and enterprises.…”
Section: Consumer Behavior Theorymentioning
confidence: 99%
“…Although green innovation can be seen as the outcome of the allocation of internal resources, this process will be also affected by organizational and macro factors (Jun et al, 2019). In terms of organizational factors, green innovation may be limited by the internal resources of enterprises (Oduro et al, 2021). Amore and Bennedsen (2016) argued that corporate governance contributes to innovation performance, and inefficient management can hinder managers' motivation for green technologies (Amore and Bennedsen, 2016).…”
Section: Green Innovationmentioning
confidence: 99%
“…This study selects control variables from financial characteristics, stock market performance, and governance characteristics, which may have a potential impact on green innovation (Chen, 2008;Amore and Bennedsen, 2016;Zhang et al, 2020;Oduro et al, 2021). The control variables include Return on assets, Current assets, Company growth, Stock return, Government subsidies, Firm age, Shareholding of the top ten shareholders, and Independent directors.…”
Section: Control Variablesmentioning
confidence: 99%
“…To achieve that, innovation is key: sustainability is hinged on innovation (Kusi-Sarpong et al , 2019). Interest in sustainable innovation has grown in recent years, both in academia and in practice (Oduro et al , 2021). As a matter of fact, if sustainable endeavors request important techno-organizational changes under the optics of the previous paradigm, innovation is the way out.…”
Section: Literature Backgroundmentioning
confidence: 99%